"There is not a safe space where they can find themselves to be free": (Un)safe spaces and the promotion of queer visibilities among township males who have sex with males (MSM) in Cape Town, South Africa. (January 2018) - Hassan, N.R.; Swartz, L.; Kagee, A.; De Wet, A.; Lesch, A.; Kafaar, Z.; Newman, P.A.
Abstract: Males who have sex with males (MSM) are prioritised in the global fight against HIV/AIDS, as a key affected population to receive HIV prevention, treatment, and HIV-related care and support (WHO, 2016 ). There is, however, limited empirical research conducted on how to engage communities of South African MSM in clinical HIV prevention research programs. The development of LGBTIQ safe spaces may potentially be a viable option to promote community-based engagement by bridging the divides between HIV-prevention researchers, marginalised queer populations, and other HIV-prevention stakeholders located in heteronormative spaces (Molyneux et al., 2016). We conducted ten in-depth, qualitative interviews with MSM safe space members who have been involved in HIV prevention research programs. Data were analysed using a thematic analytic strategy (Braun and Clarke, 2006). Our results indicate that the "safe spaces" currently operational in Cape Town are not stable spaces nor are they always safe, but they form part of a broader and much more long-term political and geographical strategy of inclusion and emancipation. Highlights: Little is known on how to engage South African MSM in clinical HIV prevention research. Developing queer safe spaces may be a viable community engagement strategy. Paradoxically, MSM safe space are unstable and unsafe in heteronormative contexts. Safe space membership promote broad-level community-based stakeholder engagement. Queer safe spaces form part of a long-term geo-political strategy of transformation.